MASYARAKAT MADANI DALAM KITAB NAHWA AL-MUJTAMA ISLAMI KARYA SAYYID QUTHB - Amaliah Farhan (Tarbawi, 2021)
This study aims to examine the concept of civil society as depicted by Sayyid Qutb in the book "Nahwa al-Mujtama' Islami". The research employs an exhaustive library research approach by collecting and evaluating data from primary texts, as well as relevant secondary literature to understand and reconstruct Qutb’s thoughts on the structure and fundamental principles of a civil society. Sayyid Qutb, a renowned Islamic thinker and theorist, put forward a conceptual framework for the development of a civilized and highly moral society, based on Islamic values and principles. In his study, Qutb emphasizes aspects such as social justice, brotherhood, individual freedom, and the rule of law as the foundations of a true civil society. The analysis of the findings indicates that Qutb's concept of civil society is deeply rooted in his understanding of the Quran and Sunnah, and addresses the contemporary challenges faced by the Muslim community. This research provides a new perspective on the dialogue between Islamic traditions and modern concepts of civil society, as well as its contributions to contemporary Islamic thought and the development of social society globally.